Case Report: Long-term follow-up of desert hedgehog variant caused 46, XY gonadal dysgenesis with multiple complications in a Chinese child - Pan, Lili; Li, Zhuoguang; Su, Zhe; Su, Wei; Zheng, Rongfei; Chen, Weiyan; He, Xuezhi; Song, Jianming; Li, Shoulin; Wen, Pengqiang (Frontiers in Genetics, 2022)
Background: Desert hedgehog (DHH), as a member of the Hedgehog (HH) family, is mainly involved in testicular development and peripheral nerve sheath formation. A DHH variant has been identified in patients with 46, XY gonadal dysgenesis (46, XY GD) with or without neuropathy, but few reports mention the involvement of other complications. Case presentation: Here, we report a Chinese female patient who was hospitalized at 14.3 years old due to slow breast development for more than one year. She had a female genitalia phenotype and started breast development at 13 years old but progressed slowly. She was not yet menarche on admission, and she had intermittent muscle cramps in her hands and feet. Her karyotype analysis was 46, XY and the SRY gene was positive. Surgical exploration revealed no uterus or ovaries, and the pathology of bilateral gonads was dysplastic testis tissue, which was consistent with partial gonadal dysplasia (PGD). Genetic analysis identified a homozygous pathogenic variant in DHH exon 3 (c.1027T>C, p. Cys343Arg). During the 6-year follow-up, she received estrogen replacement therapy resulting in breast development progression without gender dysphoria. However, her peripheral neuropathy became more obvious, and nerve conduction study (NCS) indicated decreased nerve conduction velocity and action potential. In addition, she also suffered complications such as obesity, insulin resistance, fatty liver and gastric ulcers. Conclusion: In the present study, we reported a case of 46, XY GD with minifascicular neuropathy caused by a DHH homozygous variant, and we summarized the reported cases worldwide. For the first time in such patients, we showed a comparison NCS changes with age as well as the presence of multiple complications not previously reported.